The Concept of Single Use Piston Break Safety Syringe - Mazlan, A. M.; M. R., Sapiee; Yahaya, M. S. (2014)
syringe is a simple piston pump consisting of a plunger that fits tightly in a tube. The plunger can be pulled and pushed along inside a cylindrical tube (the barrel), allowing the syringe to take in and expel a liquid or gas through an orifice at the open end of the tube. The open end of the syringe may be fitted with a hypodermic needle, a nozzle, or tubing to help direct the flow into and out of the barrel. Syringes are often used to administer injections, apply compounds such as glue or lubricant, and measure liquids. The reuse and abuse of syringe has led to cross-infection of diseases; thus, the need of single use safety syringe arises. Single use safety syringe is able to prevent the abuse of syringe. Many inventions have been produced; the most common are through-push retract breakable safety syringe, rotary plunger retractable safety syringe and release-ring breakable safety syringe. A new type of single use safety syringe Piston Break Safety Syringe is discussed in this paper. Common safety syringes available in market consist of three major components as described earlier. Beside its simplicity, the low cost to produce also the main factor why this type is very popular. The new Piston Break Safety Syringe has similar design with this widely used safety syringe; hence, it makes it easier to be adapted by the users due to its similarity, since no extra training to use it is required. The cost should be equivalently low due to the similarity in size, design and number of components.